Evolvable Components From Theory to Hardware Implementations - Sekanina, Lukas (Springer Berlin Heidelberg, 2004)
At the beginning of the 1990s research started in how to combine soft comput ing with reconfigurable hardware in a quite unique way. One of the methods that was developed has been called evolvable hardware. Thanks to evolution ary algorithms researchers have started to evolve electronic circuits routinely. A number of interesting circuits - with features unreachable by means of con ventional techniques - have been developed. Evolvable hardware is quite pop ular right now; more than fifty research groups are spread out over the world. Evolvable hardware has become a part of the curriculum at some universi ties. Evolvable hardware is being commercialized and there are specialized conferences devoted to evolvable hardware. On the other hand, surprisingly, we can feel the lack of a theoretical background and consistent design methodology in the area. Furthermore, it is quite difficult to implement really innovative and practically successful evolvable systems using contemporary digital reconfigurable technology
Keywords: Computer System Implementation; Special Purpose and Application-Based Systems; Arithmetic and Logic Structures; Computation by Abstract Devices; Computer Imaging, Vision, Pattern Recognition and Graphics; Architecture, Computer; Special purpose computers; Arithmetic and logic units, Computer; Computers; Optical data processing; Rekonfiguration; Entwurfsautomation; Field programmable gate array; Genetische Programmierung; Soft Computing; Künstliche Evolution